Evaluation of Risk and Preventive Factors for Necrotizing Enterocolitis in Premature Newborns. A Systematic Review of the Literature - Campos-Martinez, Ana M.; Expósito-Herrera, J.; Gonzalez-Bolívar, M.; Fernández-Marin, E.; Uberos, Jose (Frontiers in Pediatrics, 2022)
Necrotizing enterocolitis (NEC) is a serious condition related to prematurity and the initiation of enteral feeding. In this article, we review the evidence published in recent years on necrotizing enterocolitis risk factors (prematurity, feeding with low-weight formula, existence of intestinal dysbiosis) and protective factors (breast milk or donated milk supply, supplementation of breast milk with human milk oligosaccharides, probiotics administration, and the determination of disease predictive biomarkers). A systematic review was conducted of the risk and preventive factors for necrotizing enterocolitis in neonates prior to 37 weeks’ gestational age, based on a literature search for clinical trials, meta-analyses, randomized controlled trials and systematic reviews published between January 2018 and October 2021. For this purpose, the PubMed, MEDLINE, and Cochrane Library databases were consulted. The literature search obtained 113 articles, of which 19 were selected for further analysis after applying the inclusion and exclusion criteria. The conclusions drawn from this analysis were that adequate knowledge of risk factors that can be prevented or modified (such as alteration of the intestinal microbiota, oxidative stress, metabolic dysfunction at birth, or alteration of the immunity modulation) can reduce the incidence of NEC in premature infants. These factors include the supplementation of enteral nutrition with human milk oligosaccharides (with prebiotic and immunomodulatory effects) and the combined administration of probiotics (especially the Lactobacillus spp and Bifidobacterium spp combination, which inhibits bacterial adhesion effects, improves the intestinal mucosa barrier function, strengthens the innate and adaptive immune system and increases the secretion of bioactive metabolites). The supplementation of human milk with lactoferrin, the use of donated milk fortified in accordance with the characteristics of the premature newborn and the determination of factors that can predict the existence of NEC, such as fecal calprotectin, increased TLR4 activity, and IL6 receptor, can all modify NEC outcomes. Although further studies should be conducted to determine the values of predictive biomarkers of NEC, and/or the recommended doses and strains of probiotics, lactoferrin or oligosaccharides, the knowledge acquired in recent years is encouraging.